A Study on Unemployment rate of Youth Graduates Student in Malaysia - Kia Hui Gan; Kok Ban Teoh; Zong Bin Cheah; Wan Xin Teh; Qing Yee Tan; Ningze Ng; Yi Lin Goh; Kumari Prerna; Snehal Deepak Kanoujiya (AIBPM Publisher, 2024)
This study delves into the dynamics of unemployment rate among recent graduates within the first two years post-graduation. By employing Partial Least Square (PLS) as a statistical tool, the research aims to assess both the measurement and structural models, providing valuable insights into the factors influencing unemployment. This research aims to investigate how English proficiency, employability skills and job mismatch affect unemployment rate among youth graduate students in Malaysia. This quantitative research distributed an online questionnaire to collect data from 300 unemployed youth graduate students. The findings implies that English proficiency and job mismatch have significant positive relationship with unemployment rate, whereas employability skills possess a significant negative relationship with unemployment rate. The findings contribute to the continuous improvement on unemployment rate among the youth graduate students of Malaysia by English proficiency, employability skills and job mismatch